Analisis faktor-faktor yang mempengaruhi perilaku kader terhadap penemuan suspek TB paru di Puskesmas Panombeian Panei Kabupaten Simalungun tahun 2020 - Patrice Armando Sipayung; Asriwati Asriwati; Tengku Moriza (Journal of Pharmaceutical and Sciences, 2023)
Introduction: According Global TB Report in 2018, there were 842,000 new cases of pulmonary TB (319/100,000 people) and 116,000 fatalities from pulmonary TB (44/100,000 people), including those who were HIV-positive. Objective: The stuay aimed to determine the most important characteristics that will affect the detection of TB suspects at Panombeian Panei Health Centre in 2020, including age, education, occupation, knowledge, attitudes, distance, family support, counseling, and cadre compensation. Method: This stuay was analytic study. The sample was 132 health centre cadres from population of 196 by using proportional and random sampling methods. Univariate, bivariate with chi-square test, and multivariate with logistic regression test were utilized in the data analysis. The Result: The p-value of age (0.059 OR 1.426), occupation (0.008 OR 0.055), knowledge (0.026 OR 2.899), attitude (0.821 OR 1.756), distance (0.041 OR 2.593), family support (0.038 OR 2.617), counseling (0.620 OR 1.297), compensation (0.004 OR 6,475). Conclusion: The findings showed that identification of TB suspects was influenced by employment, knowledge, distance, family support, and compensation but not by age, education, attitude, or counseling. It is advised that the local government improve the dedication to collaboration with connected parties such health agencies, sub-districts, business sector, non-governmental organizations, health and religious groups.